Instabilidade e Queda Presidencial em Perspectiva Comparada: um Estudo de Caso Mais-similar Sobre Os Governos Kirchner (2007-2015) e Rousseff (2011-2016) - Oliveira, Wanderlea Almenara Merlo Emmerick (2021)
A set of variables has been raised in the literature to explain the dismissal of Latin American presidents since the 1990s, within it economic crisis, neoliberal politics, corruption scandals, street protests, media performance and loss of parliamentary s